2021
DOI: 10.1016/j.ijscr.2021.106507
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal wall endometriosis: A challenging iatrogenic disease

Abstract: Introduction and importance Abdominal wall endometriosis is a rare clinical condition associated with abdominal pain and psychologic disorders. It's pathophysiology remains unclear. Clinical history and imaging findings are necessary for the diagnosis. Its management is challenging, and requires close collaboration between gynaecologists and visceral surgeons specially in complex procedures. The aims of our study are to present risk factors, clinical presentation, imaging findings and management f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Diagnosis of abdominal wall lesions is difficult and often delayed because it usually does not present with the classic symptoms of endometriosis. 8 In a case control study of 25 patients with abdominal wall endometriosis, Ferjaoui et al 22 found that the only common symptom in all patients was cyclic pelvic pain. Marras et al 23 concluded the same in an 11-year retrospective study of endometriosis patients with involvement of the abdominal wall, highlighting the nonspecific nature of symptoms in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of abdominal wall lesions is difficult and often delayed because it usually does not present with the classic symptoms of endometriosis. 8 In a case control study of 25 patients with abdominal wall endometriosis, Ferjaoui et al 22 found that the only common symptom in all patients was cyclic pelvic pain. Marras et al 23 concluded the same in an 11-year retrospective study of endometriosis patients with involvement of the abdominal wall, highlighting the nonspecific nature of symptoms in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound and MRI are two accessible and reliable imaging tests, visualizing the parietal heterogeneous mass [3]. The intraoperative specific aspect of endometrioma is characterized by the abundant, firm fibrosis that invades the adjacent structures, without a clear limit, usually with the presence of sites containing brown liquid, representing a source of irritation that triggers the strong local inflammatory reactions, marked by fibrosis, with a cyclical evolution [7].…”
Section: Discussionmentioning
confidence: 99%
“…Parietal Endometriosis(PE) is one of the rarest pathological feature of endometriosis [1], which mostly affects women of reproductive age, caused by the presence of ectopic islets of endometrial active cells on the abdominal wall, after surgical or gynecological procedures [2]. Its physiopathology remains under debate till this date [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging modalities to aid in the diagnosis of scar endometriosis include magnetic resonance imaging (MRI), ultrasonography (US), and computed tomography (CT), with US generally being the initial imaging modality of choice given its cost and availability. The lesions appear to be hypoechoic and heterogenous with echogenic spots [ 24 ]. Scar endometriomas on CT appear as well-circumscribed, enhancing, solid, soft-tissue masses when intravenous contrast is used [ 25 ].…”
Section: Discussionmentioning
confidence: 99%